Analisis Yuridis Catcalling sebagai Kekerasan Seksual dalam Pasal 5 UU Nomor 12 Tahun 2022 Perspektif Maqasid al-Syari’ah - Annisa Izzatul Jannah; Ismail Ismail (Lembaga Yasin AlSys, 2026)
The phenomenon of catcalling as a form of verbal sexual harassment is often considered trivial, even though it causes serious psychological impacts on victims. This study aims to analyze catcalling as a form of sexual violence from the perspective of Article 5 of Law Number 12 of 2022 concerning Sexual Violence Crimes and to examine it based on maqashid al-syari’ah. This study used a juridical legal research method with a statutory approach and a conceptual approach. The research data consisted of primary, secondary, and tertiary legal materials analyzed qualitatively. The results showed that catcalling can be classified as a form of sexual violence as regulated in Article 5 of the Sexual Violence Crimes Law because it fulfills the elements of an act that is sexual in nature, is carried out without consent, and causes victims to feel uncomfortable, ashamed, and afraid. From the perspective of maqashid al-syari’ah, the act of catcalling is contrary to the objectives of the sharia, particularly in safeguarding honor (hifz al-‘ird), safeguarding life (hifz al-nafs), and safeguarding intellect (hifz al-‘aql). This study emphasizes that the regulation of catcalling in Indonesian positive law is in line with the values of protection in Islamic law. The conclusion of the study emphasizes the importance of firm law enforcement against perpetrators of catcalling as well as increasing public awareness to create a safe and dignified environment, so that protection for victims becomes not only the responsibility of the state, but also part of the effort to realize public benefit in social life.